2005
DOI: 10.1074/jbc.m411076200
|View full text |Cite
|
Sign up to set email alerts
|

Use of Photoaffinity Labeling and Site-directed Mutagenesis for Identification of the Key Residue Responsible for Extraordinarily High Affinity Binding of UCN-01 in Human α1-Acid Glycoprotein

Abstract: 7-Hydroxystaurosporine (UCN-01

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 63 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…In addition to this region, amino acid residues in the regions surrounding positions 25 and 160 are also involved in drug binding to AGP. Previously, we observed that UCN‐01 has the greatest binding affinity for AGP, and does not selectively bind to AGP variants 14. This observation suggests that amino acid residues located near W160 that significantly contribute to UCN‐01 binding may not play an important role in drug‐binding selectivity.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition to this region, amino acid residues in the regions surrounding positions 25 and 160 are also involved in drug binding to AGP. Previously, we observed that UCN‐01 has the greatest binding affinity for AGP, and does not selectively bind to AGP variants 14. This observation suggests that amino acid residues located near W160 that significantly contribute to UCN‐01 binding may not play an important role in drug‐binding selectivity.…”
Section: Discussionmentioning
confidence: 84%
“…Using a photoaffinity labeling, we found that residues in the Y91‐R105 range of the F1*S variant are involved in flunitrazepam binding 12. In addition, W25 and W160 play important roles in the binding of progesterone and UCN‐01, respectively 13, 14. Recently, Zsila and Iwao15 also found that W25 is involved in drug binding to AGP based on induced circular dichroism spectra.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Attempts to map the amino acids involved in drug binding of hAGP have been made using a range of different experimental approaches, including fluorescent probe displacement (12), chemical modification (13,14), photoaffinity labeling (15,16), and other spectroscopic methods (17). However, most of these investigations used mixtures of hAGP variants, resulting in some contradictory results.…”
mentioning
confidence: 99%
“…We reported that dog albumin is suitable for investigating drug-drug interactions on site II, whereas rat, rabbit, and bovine albumins are suitable for examining the binding of site I drugs (Kosa et al, 1997). Based on that study we attempted to elucidate the structural configuration of the binding site of dog albumin that resembles site II of HSA, using a photoaffinity labeling method (Garabedian and Yount, 1991;Chuang et al, 1999;DeSantis et al, 2000;Katsuki et al, 2005).…”
Section: Discussionmentioning
confidence: 99%